THE RELEVANCE OF THE MUSEUM OF FAVELAS FOR AN INTERCULTURAL AND DECOLONIAL EDUCATION (Citizenship in Action: Extension and Culture Magazine, 2025)
This article examines the contributions of the Museum of Favelas to intercultural and decolonial education, analyzing its role as a cultural institution dedicated to promoting epistemic plurality. Founded as an institution committed to valuing peripheral cultures and deconstructing Eurocentric narratives, the Museum has established itself as a reference in amplifying historically silenced voices. Based on visits and studies conducted in 2023, a period of intensified activity, it was observed how its cultural and educational initiatives fostered the re-signification of urban territories, the appreciation of Afro-Brazilian and Indigenous knowledge, and the empowerment of peripheral communities. However, with the transition to a conservative state government aligned with far-right political agendas, the Museum underwent a process of dismantling and underutilization as a public policy. This context not only compromised its operational structure but also contradicted its original mission as a space for inclusion and decolonization, illustrating the impacts of political and ideological shifts on the management of transformative cultural initiatives. Anchored in the frameworks of critical interculturality and decolonial pedagogy, this study articulates theoretical and empirical analyses, highlighting the Museum’s relevance as a locus of resistance and reflection. Despite the challenges imposed, the Museum of Favelas remains a symbol of the struggle for cultural diversity and historical reparation in Brazil, reaffirming the need for public policies that ensure the continuity of cultural spaces committed to intercultural dialogue and the construction of a plural education.
Keywords: Interculturality; Decoloniality; Museum Education; Peripheral Cultures